Neuromuscular status and training load during 1 week of international training camp: the case of the U-21 football national team from the Czech Republic - Hrubý, M.; Paludo, A. C. (Sport Sciences for Health, 2024)
The study aimed to describe the neuromuscular status and training load in the U-21 soccer football from the Czech Republic during an international training camp. Sixteen players were sampled with data from the neuromuscular status by countermovement jump (CMJ), external load by global positioning system (GPS) parameters and internal load by session rate of perceived exertion (RPE). The camp consisted of 5 days of field training and 2 days of friendly matches. CMJ was performed on days 1, 4 and 7. The comparison of variables during the camp was tested by the Friedman test, one-way repeated measure ANOVA, effect size (ES) and percentage of change (p < 0.05). A significant improvement of 6% in jump performance was found from day 1 (49.7 ± 3.98 cm) to day 7 (52.8 ± 4.52 cm) (p < 0.001), with a moderate effect (ES = 0.7). Both internal and external loads presented significant variation during the camp, with higher RPE and GPS parameters on the day of the friendly matches = day 4 and day 7 and lower load on days 5 and 6 (p < 0.05). The study provides a report on a positive neuromuscular status in the Czech football players during an international camp including a congested and competitive fixture, presenting an undulation on training loads across the training sessions, with higher loads on the match days. This study demonstrated that the periodization used by the Czech national football team in this specific congested fixture seems to not impair the neuromuscular status.